Porous membrane as well as preparation method and application thereof
By using ultraviolet laser hole drilling in the electrolyte membrane of lithium batteries, using specific composite structures and pore structures, the battery short circuit and self-discharge problems caused by high pore throughput in the prior art are solved, and the battery short circuit and self-discharge problems are improved. Battery safety and cycle performance.
Patent Information
- Application Number
- CN202411246121.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-06
AI Technical Summary
The porous membrane of existing solid-state lithium batteries is formed by direct punching, resulting in high pore throughput, resulting in poor liquid retention rate of the separator, which is prone to short-circuiting and self-discharge of the battery.
The porous membrane is formed by ultraviolet laser drilling. By providing a specific composite structure and pore structure in the electrolyte membrane, it includes the first, second and third porous membrane layers stacked in sequence, and the pore size of the second porous membrane layer is larger than that of the first The pore size of the first and third porous membrane layers is added, and an ultraviolet absorber is added to the intermediate layer to improve the torsion and surface flatness of the pores.
Effectively reduce the contact probability of positive and negative electrodes, improve the liquid retention rate of the diaphragm, improve the safety and circulation performance of the battery, and avoid battery short circuit and self-discharge.
Smart Images

Figure CN119116512A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of materials and relates to a porous membrane and a preparation method and application thereof. Background Art
[0002] Commercial lithium-ion batteries currently mainly use organic liquid electrolytes. However, due to the characteristics of organic solvents being flammable, easy to leak, and easy to volatilize, there are potential risks such as battery overcharging and short circuits, which make liquid organic electrolyte lithium-ion batteries have certain safety hazards in use. All-solid-state lithium batteries are expected to solve safety problems such as electrolyte leakage, combustion, and short circuits caused by lithium dendrites piercing the diaphragm in liquid lithium batteries.
[0003] At present, the mainstream solid electrolyte membrane is usually obtained by punching the film. Conventional laser drilling uses a high-power density laser beam to irradiate the processed material, so that the material is quickly heated to the vaporization temperature and evaporates to form holes. However, the holes formed by direct punching have high direct penetration, and the obtained porous membrane has poor liquid retention when used in the diaphragm, which is easy to cause a high battery short circuit rate and obvious self-discharge. Summary of the invention
[0004] The present invention provides a porous membrane. The specific composite structure and pore structure of the porous membrane are applied to an electrolyte membrane to reduce the contact probability between positive and negative electrodes and the self-discharge phenomenon of the battery, and can increase the liquid retention rate of the diaphragm, thereby improving the safety performance and cycle performance of the battery.
[0005] The present invention also provides a method for preparing a porous membrane. The method adopts ultraviolet laser drilling to form a porous membrane, and can efficiently prepare a porous membrane. The porous membrane has high surface flatness and mechanical strength while meeting a specific pore structure.
[0006] The present invention also provides an electrolyte membrane and a battery. Since the electrolyte membrane includes the above-mentioned porous membrane, it has a high liquid retention rate and can also avoid the self-discharge of the battery and the short circuit caused by the contact between the positive and negative electrodes, so that the battery has higher safety performance and cycle performance.
[0007] The present invention provides a porous membrane, comprising a first porous membrane layer, a second porous membrane layer and a third porous membrane layer stacked in sequence;
[0008] The first porous membrane layer includes a first through hole, the second porous membrane layer includes a second through hole, and the third porous membrane layer includes a third through hole;
[0009] The first through hole, the second through hole and the third through hole are coaxially arranged, and the aperture of the second through hole is larger than the apertures of the first through hole and the third through hole.
[0010] The porous membrane as described above, wherein the thickness of the second porous membrane layer is 1 to 10 times the thickness of the first porous membrane layer and / or the third porous membrane layer.
[0011] The porous membrane as described above, wherein the ratio of the pore size of the first through hole and / or the third through hole to the pore size of the second through hole is greater than or equal to 0.1 and less than 1.
[0012] The porous membrane as described above, wherein the second porous membrane layer comprises an ultraviolet absorber;
[0013] Preferably, the mass content of the ultraviolet absorber in the second porous membrane layer is 0.1% to 2%.
[0014] The porous membrane as described above, wherein the materials of the first porous membrane layer, the second porous membrane layer and the third porous membrane layer independently include one or more of polyethylene terephthalate, polyimide, polybutylene terephthalate, polyethylene naphthalate, polyetheretherketone, polyphenylene sulfide, and polybenzimidazole.
[0015] A second aspect of the present invention provides a method for preparing the porous membrane as described above, comprising the following steps:
[0016] 1) co-extruding at least three layers of polymer melts by casting or blow molding to obtain a composite film, wherein the ultraviolet absorption ability of the polymer melt in the middle layer is stronger than that of the polymer melt in the surface layer;
[0017] 2) Using an ultraviolet laser light source to perform laser drilling on the composite membrane to obtain the porous membrane.
[0018] The preparation method as described above, wherein the content of the ultraviolet absorber in the polymer melt located in the middle layer is greater than that in the polymer melt located in the surface layer;
[0019] Preferably, the mass content of the ultraviolet absorber in the middle layer is 0.1% to 2%.
[0020] The preparation method as described above, wherein the ultraviolet laser light source is selected from one or more of a rare gas excimer laser, a rare gas halide excimer laser, and a halogen gas excimer laser;
[0021] And / or, the power of a single light source for the laser drilling process is 0.5W to 20W.
[0022] The third aspect of the present invention provides an electrolyte membrane, comprising the porous membrane provided by the first aspect of the present invention or a porous membrane prepared by the preparation method provided by the second aspect of the present invention.
[0023] A fourth aspect of the present invention provides a battery, comprising the electrolyte membrane provided by the third aspect of the present invention.
[0024] The implementation of the present invention has at least the following advantages:
[0025] 1) The porous membrane provided by the present invention has a composite structure of a first porous membrane layer, a second porous membrane layer and a third porous membrane layer stacked in sequence, wherein the pore size of the second through hole in the middle second porous membrane layer is larger than the pore size of the first through hole in the first porous membrane layer and the third through hole in the third porous membrane layer coaxially arranged therewith, so that the pores of the porous membrane have a certain tortuosity. Applying it to the electrolyte membrane can reduce the contact probability of the positive and negative electrodes and the self-discharge phenomenon of the battery, thereby making the battery have higher safety performance. In addition, the structure of the porous membrane with large pores in the middle layer and small pores in the upper and lower surface layers is conducive to the storage of the electrolyte, which is conducive to improving the liquid retention rate of the diaphragm and improving the cycle performance of the battery.
[0026] 2) The method for preparing the porous membrane provided by the present invention can efficiently prepare the porous membrane by selecting a membrane material with strong ultraviolet absorption ability as the middle layer and then using ultraviolet laser punching to obtain the porous membrane. Due to the lower thermal effect of the ultraviolet laser, the melt accumulation on the surface of the porous membrane can be avoided, so that the prepared porous membrane has higher surface flatness and mechanical strength.
[0027] 3) The electrolyte membrane provided by the present invention includes the above-mentioned porous membrane with a certain porosity, so the diaphragm can reduce the contact probability between the positive and negative electrodes and the self-discharge phenomenon of the battery, thereby making the battery have higher safety performance, and the middle layer of the porous membrane has pores with larger pore sizes than the upper and lower surface membranes, which is more conducive to the storage of the electrolyte.
[0028] 4) The battery provided by the present invention has the advantages of high safety performance and good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 30000 times SEM image of the cross section of the porous membrane of Example 2 of the present invention;
[0030] Figure 2 This is a 100,000-fold SEM image of the cross section of the porous membrane of Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] A first aspect of the present invention provides a porous membrane, comprising a first porous membrane layer, a second porous membrane layer and a third porous membrane layer stacked in sequence;
[0033] The first porous membrane layer includes a first through hole, the second porous membrane layer includes a second through hole, and the third porous membrane layer includes a third through hole;
[0034] The first through hole, the second through hole and the third through hole are coaxially arranged, and the aperture of the second through hole is larger than the apertures of the first through hole and the third through hole.
[0035] The porous membrane of the present invention increases the internal tortuosity of the pores in the porous membrane by limiting the pore size of the second through hole in the second porous membrane layer located in the middle to be larger than the pore sizes of the first through hole and the third through hole. The larger pore size in the second through hole in the middle layer is conducive to storing electrolyte, thereby reducing the short circuit probability of the battery, inhibiting the self-discharge of the battery, and making the battery have higher safety performance.
[0036] The present invention does not limit the number of first through holes, second through holes and third through holes, which can be selected according to different requirements for the porosity of the porous membrane. The higher the porosity requirement, the more first through holes, second through holes and third through holes can be set.
[0037] The first porous membrane layer, the second porous membrane layer and the third porous membrane layer of the present invention can be respectively composed of a single polymer film or a plurality of polymer films. Taking the first porous membrane layer as an example, it can be composed of a single polymer film or a plurality of polymer films.
[0038] In a preferred embodiment, the thickness of the second porous membrane layer is 1 to 10 times the thickness of the first porous membrane layer and / or the third porous membrane layer.
[0039] Specifically, the thickness of the second porous membrane layer may be 5 to 20 μm, and the thickness of the first porous membrane layer and / or the third porous membrane layer may be 0.5 to 20 μm. Exemplarily, the thickness of the second porous membrane layer may be 5 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, or a range consisting of any two of the above values; the thickness of the first porous membrane layer and / or the third porous membrane layer may be 0.5 μm, 2 μm, 5 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, or a range consisting of any two of the above values.
[0040] In a preferred embodiment, the ratio of the aperture of the first through hole and / or the third through hole to the aperture of the second through hole is greater than or equal to 0.1 and less than 1. By setting the aperture of a specific ratio, the porous membrane can have good mechanical strength while further reducing the probability of battery short circuit, inhibiting the self-discharge of the battery, and making the battery have higher safety performance.
[0041] Furthermore, the second porous membrane layer includes an ultraviolet absorber. The ultraviolet absorption capability of the second porous membrane layer can be enhanced by including the ultraviolet absorber in the second porous membrane layer.
[0042] The present invention does not specifically limit the type of ultraviolet absorber, which can be selected from the ultraviolet absorbers commonly used in the art, including but not limited to one or more of o-hydroxybenzoic acid phenyl ester, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole (UV-P), hydroxybenzophenone, and 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole (UVP-327). The above ultraviolet absorbers not only have strong ultraviolet absorption capacity, but also have good compatibility with conventional polymer film materials, which is conducive to the processing of porous membranes.
[0043] In addition to the ultraviolet absorber included in the second porous film layer, ultraviolet absorbers can also be added to the first porous film layer and the third porous film layer according to the different absorption capacities of the film material to the ultraviolet light source. For example, when the absorption capacities of the first porous film layer and the third porous film layer to the ultraviolet light source are relatively weak, ultraviolet absorbers can be added thereto to enhance the absorption of the film material to the ultraviolet light source, so as to improve the efficiency of the punching.
[0044] In a specific embodiment, the mass content of the ultraviolet absorber in the second porous film layer is 0.1% to 2%. Exemplarily, the mass content of the ultraviolet absorber in the second porous film layer can be 0.1%, 0.3%, 0.5%, 0.8%, 1.0%, 1.5%, 2.0% and a range consisting of any two values therein. When the content of the ultraviolet absorber is lower than 0.1%, it is difficult to effectively improve the ultraviolet absorption capacity of the second porous film layer, resulting in no significant difference between the pore size of the second porous film layer located in the middle layer and the surface layer. When the content of the ultraviolet absorber is greater than 2.0%, the ultraviolet absorption capacity of the second porous film layer is too strong, resulting in the pore size of the second porous film layer located in the middle layer being too large, which is detrimental to the mechanical strength of the porous film.
[0045] In a specific embodiment, the materials of the first porous membrane layer, the second porous membrane layer and the third porous membrane layer independently include one or more of polyethylene terephthalate, polyimide, polybutylene terephthalate, polyethylene naphthalate, polyetheretherketone, polyphenylene sulfide and polybenzimidazole. The above polymers all have good heat resistance, which can make the prepared porous membrane have better thermal stability and not easy to shrink under heating.
[0046] A second aspect of the present invention provides a method for preparing the porous membrane as described above, comprising the following steps:
[0047] 1) co-extruding at least three layers of polymer melts by casting or blow molding to obtain a composite film, wherein the ultraviolet absorption ability of the polymer melt in the middle layer is stronger than that of the polymer melt in the surface layer;
[0048] 2) The composite film is subjected to laser punching treatment using an ultraviolet laser light source to obtain a porous film.
[0049] Since the ultraviolet absorption ability of the polymer melt in the middle layer is stronger than that of the polymer melt in the surface layer, when the composite membrane is laser punched with an ultraviolet laser light source, the polymer melt in the middle layer absorbs the ultraviolet laser light source better, and the melting area of the membrane material is larger than that of the surface layer. Therefore, the aperture of the second through hole formed is larger than the apertures of the first through hole and the second through hole, thereby obtaining a porous membrane with obvious internal tortuosity.
[0050] In addition, compared with the traditional operation of using an infrared laser light source for drilling, the above preparation process uses an ultraviolet laser light source for drilling. The ultraviolet laser light source has a lower thermal effect and can avoid the accumulation of molten material on the surface of the porous membrane during the drilling process, so that the porous membrane has a higher flatness and a more uniform internal stress distribution. The more uniform internal stress distribution can enable the porous membrane to maintain a higher mechanical strength.
[0051] The above preparation method can be used to prepare a porous membrane with a large pore structure in the middle layer and small pore structures in the upper and lower layers of the middle layer. The pores of the porous membrane have a certain internal tortuosity and low straightness, which is beneficial to increase the liquid retention capacity of the electrolyte, reduce the probability of direct contact between the positive and negative electrodes and short circuit and the self-discharge of the battery, and improve the safety performance and cycle performance of the battery.
[0052] In a specific embodiment, the content of ultraviolet absorber in the polymer melt located in the middle layer can be made greater than that in the polymer melt located in the surface layer so that the ultraviolet absorption ability of the polymer melt located in the middle layer is stronger.
[0053] Preferably, the mass content of the ultraviolet absorber in the polymer melt in the middle layer is 0.1% to 2%. Exemplarily, the mass content of the ultraviolet absorber in the polymer melt in the middle layer can be 0.1%, 0.3%, 0.5%, 0.8%, 1.0%, 1.5%, 2.0% and a range consisting of any two of these values.
[0054] The present invention does not specifically limit the type of ultraviolet laser light source, and a conventional ultraviolet laser light source may be selected, for example, one or more of a rare gas excimer laser, a rare gas halide excimer laser, and a halogen gas excimer laser. Specifically, the rare gas excimer laser may be a Xe2 excimer laser or an Ar2 excimer laser, the rare gas halide excimer laser may be an ArF excimer laser, a KrF excimer laser, or a XeCl excimer laser, and the halogen gas excimer laser may be an F2 excimer laser. Specifically, an ultraviolet laser light source of a corresponding wavelength may be selected according to the required aperture.
[0055] The present invention does not specifically limit the device for laser drilling processing, and the laser drilling processing can be performed by selecting a conventional laser drilling device in the art. For example, an array laser drilling device can be used for drilling.
[0056] The power of the light source is also an important factor affecting the quality of the prepared porous membrane. If the power is too high, it is easy to produce a strong thermal effect, resulting in the accumulation of melt on the surface of the porous membrane. If the power is too low, it is difficult to achieve the required processing efficiency. Based on the above considerations, the power of a single light source for laser punching is preferably 0.5W to 20W. Among them, the power of a single light source refers to the power of a single excited state optical element during dot matrix punching or dense punching. Exemplarily, the power of a single light source can be 0.5W, 1W, 3W, 5W, 8W, 10W, 13W, 15W, 18W, 20W or a range consisting of any two of these values.
[0057] The third aspect of the present invention provides an electrolyte membrane, comprising the porous membrane of the first aspect of the present invention or a porous membrane prepared by the preparation method of the second aspect of the present invention.
[0058] Since the pores of the porous membrane have a certain degree of tortuosity, it can be used as an electrolyte to reduce the contact probability between the positive and negative electrodes and avoid the self-discharge of the battery, thereby reducing the short circuit probability of the battery and improving the safety performance of the battery. In addition, since the pore size inside the porous membrane is larger than the pore size on the surface, it is more conducive to the storage of the electrolyte. The membrane can be used in liquid batteries to increase the liquid retention capacity of the battery and thus help improve the cycle performance of the battery.
[0059] The electrolyte membrane of the present invention can be the above-mentioned porous membrane directly as a diaphragm, or a functional layer can be coated on its surface to form a composite diaphragm according to different battery functional requirements. For example, for batteries with higher safety performance requirements, ceramic slurry can be coated on the surface of the porous membrane to form a ceramic layer, and the high heat resistance of the ceramic can be used to further improve the safety performance of the battery.
[0060] In addition, for the porous membrane formed by laser drilling, the average pore size of the obtained porous membrane is larger, which is more suitable for application in solid-state batteries or semi-solid-state batteries. In a specific embodiment, a solid electrolyte can be coated inside the pores of the porous membrane and on the surface of the porous membrane to improve the ion conductivity of the electrolyte membrane, thereby improving the rate performance of the battery.
[0061] The present invention does not specifically limit the type of the above-mentioned solid electrolyte, which can be selected from solid electrolytes conventionally used in the art, including but not limited to one or more of oxide solid electrolytes, polymer solid electrolytes, sulfide solid electrolytes, and gel electrolytes. Among them, the oxide solid electrolyte is preferably aluminum titanium phosphate (LATP) or lithium lanthanum zirconium oxide (LLZO), the polymer solid electrolyte is preferably copolymer-modified polyethylene oxide (PEO), and the sulfide solid electrolyte is preferably Li6PS5Cl.
[0062] The fourth aspect of the present invention provides a battery, comprising the electrolyte membrane provided by the third aspect of the present invention. Since the electrolyte membrane has a certain internal tortuosity, the probability of direct contact between the positive and negative electrodes and the self-discharge phenomenon of the battery can be reduced. Therefore, the battery has higher safety performance.
[0063] The porous membrane provided by the present invention and its preparation method and application will be further described in detail below through specific examples. Obviously, the following examples are only some embodiments of the present invention, not all embodiments. Based on the technical solutions and given embodiments provided by the present application, all other embodiments obtained by those skilled in the art without creative work are within the protection scope of the present invention.
[0064] Example 1
[0065] This embodiment provides a porous membrane, a separator and a lithium ion battery, and the specific preparation method is as follows:
[0066] 1. Preparation of porous membrane
[0067] 1) placing a first film material (made of PET, with a thickness of 2.5 μm), a second film material (a PET film containing 0.5% phenyl o-hydroxybenzoate, with a thickness of 5 μm), and a third film material (made of PET, with a thickness of 2.5 μm) in sequence, and performing thermal lamination at 120° C. to obtain a composite film;
[0068] 2) The composite membrane is subjected to laser drilling treatment using an array laser device to obtain a porous membrane; wherein the light source for the laser drilling treatment is selected from an ArF excimer laser light source, the laser wavelength is 193nm, and the single light source power is 5W.
[0069] 2. Preparation of solid electrolyte membrane
[0070] 1) adding 50 parts by weight of solid electrolyte powder LATP, 0.5 parts by weight of thickener CMC, 0.25 parts by weight of dispersant BYK-156, 5 parts by weight of adhesive GR401, 0.1 parts by weight of wetting agent BYK-348, and 50 parts by weight of deionized water into a double planetary slurry kettle, stirring at 2000 rpm / min for 120 min to obtain a coating slurry;
[0071] 2) The above coating slurry is coated onto the porous membrane prepared in step 1 by a dip coating process, and then dried at a temperature of 60° C. to 80° C. to obtain a solid electrolyte membrane.
[0072] 3. Preparation and assembly of batteries
[0073] 1) The positive electrode active material NCM811, the conductive agent SP, the conductive agent KS-6, and the binder PVDF are mixed in a solvent NMP in a mass ratio of 90:2:1:3 to form a positive electrode slurry, which is then coated on a 10 μm aluminum foil current collector; then dried in an oven at 95°C, and rolled on a roller press for use.
[0074] 2) The active material artificial graphite, the conductive agent acetylene black and the binder CMC / SBR (mass ratio of 1:1) are evenly dispersed in water at a mass ratio of 90:5:5 to form a negative electrode slurry, which is coated on a copper foil current collector with a thickness of 10 μm, dried in an oven at 85°C, and rolled on a roller press for use.
[0075] 3) In a drying room with a dew point of <-40°C, the solid electrolyte composite membrane of the present invention is placed between the positive electrode sheet and the negative electrode sheet for stacking and packaging, and the solid electrolyte composite membrane is heated at 2.5 g / m 2 The electrolyte (Xinzhoubang, LBC3008A) was injected in a proportion of to obtain a battery.
[0076] Examples 2 to 7 and Comparative Example 1
[0077] Examples 2 to 7 and Comparative Example 1 respectively provide a porous membrane, a solid electrolyte membrane and a lithium ion battery, wherein the conditions in the preparation process of the porous membrane are basically the same as those in Example 1, and the differences are listed in Table 1. The preparation conditions of the solid electrolyte membrane and the lithium ion battery are the same as those in Example 1, and are not repeated here.
[0078] Table 1
[0079]
[0080] The porous membranes prepared in Example 2 and Comparative Example 1 were subjected to SEM testing. Figure 1 The 30000 times SEM image of the porous membrane cross section of Example 2 is as follows: Figure 1 As shown, the pore structure of the porous membrane is large in the middle and narrow on both sides, and the bulges on both sides of the porous membrane are effectively controlled; Figure 2 The 100000 times SEM image of the porous membrane cross section of Comparative Example 1 of the present invention is as follows: Figure 2 As shown, the pore structure of the porous membrane of Comparative Example 1 is relatively straight and has no obvious tortuosity.
[0081] Test Case
[0082] 1. The following properties of the porous membranes of the above embodiments and comparative examples were tested:
[0083] 1. Average thermal shrinkage at 200℃
[0084] Test method: Referring to GB / T36363-2018, the porous membrane was placed in a 200°C environment, treated for 1 hour, and the thermal shrinkage in MD and TD directions was calculated. The average value of the thermal shrinkage in MD and TD directions was taken as the average thermal shrinkage at 200°C.
[0085] 2. MD tensile strength
[0086] Test method: refer to GB / T36363-2018.
[0087] 3. Puncture strength
[0088] Test method: refer to GB / T36363-2018.
[0089] 4. Porosity
[0090] Test method: refer to GB / T36363-2018.
[0091] 5. The apertures of the first through hole, the second through hole, and the third through hole
[0092] Test method: It can be calculated by electron microscopy or microscope field of view of the cross section or surface combined with image processing software. The first through hole, the second through hole and the third through hole refer to the through hole in the first porous membrane layer, the through hole in the second porous membrane layer and the through hole in the third porous membrane layer, respectively.
[0093] 2. The following performance tests were performed on the solid electrolyte membranes of the above embodiments and comparative examples:
[0094] 1. Insulation strength
[0095] Test method: Place the solid electrolyte membrane between two electrodes, apply voltage between the electrodes, increase the voltage until the solid electrolyte membrane is broken down, and take the voltage value when the solid electrolyte membrane is broken down, which is the insulation strength.
[0096] The test results of the above performance are shown in Table 2.
[0097] 3. The batteries prepared in the above examples and comparative examples were tested for the following properties:
[0098] 1. Energy density
[0099] Test method: Test the soft-pack battery in the voltage range of 3.0V to 4.5V. The discharge platform voltage can be determined by cyclic voltammetry at a rate of 0.5C. Then, discharge at a constant current of 1C in a fully charged state to measure the discharge capacity. The volume energy density is calculated by the following formula:
[0100]
[0101] 2. Short circuit rate
[0102] Five battery cells with a capacity of 2Ah were prepared for each solid electrolyte membrane. The battery short circuit was tested at a voltage of 100V using a Zhongce ZC5520 battery cell short circuit tester without liquid injection, where the short circuit rate = number of short-circuited battery cells / 5×100%.
[0103] 3. Capacity retention rate after 200 cycles at 25℃
[0104] At 25°C, the first-round discharge capacity was measured at 0.5C charge / 0.5C discharge. At the same time, the ratio of the discharge capacity measured after 200 cycles to the first-round discharge capacity was calculated under this condition as the capacity retention rate after 200 cycles at 25°C.
[0105] The test results of all the above performances are shown in Table 2.
[0106] Table 2
[0107]
[0108] The following conclusions can be drawn from Table 2:
[0109] 1) By comparing Example 1 and Example 2, it can be seen that compared with PET, PVDF has stronger ultraviolet absorption ability and a larger pore size of its second porous membrane layer. Accordingly, the average thermal shrinkage rate of the porous membrane at 200°C is higher, the puncture strength and the insulation strength of the solid electrolyte membrane side are reduced, but the volume energy density and cycle performance of the battery are improved.
[0110] 2) By comparing Examples 1, 3, and 4, it can be seen that when the thickness ratio of the first film layer and the third film layer to the second film layer is too small (Example 3), although the puncture strength of the porous membrane and the insulation strength of the solid electrolyte membrane are significantly increased, the volume energy density of the battery is significantly reduced, and the short circuit rate of the battery cell is improved; when the thickness ratio of the first film layer and the third film layer to the second film layer is too large (Example 4), the roughness of the surface of the porous membrane is significantly increased, the volume energy density of the battery is also significantly reduced, and the battery cell has a certain short circuit rate, but the puncture strength of the porous membrane and the insulation strength of the solid electrolyte membrane are increased, and as the thickness ratio of the second film layer decreases, the internal tortuosity of the porous membrane is reduced, and the directness of the pores is improved, thereby improving the short circuit rate of the battery.
[0111] 3) By comparing Examples 1 and 5, it can be seen that when too much ultraviolet absorber is added to the second film layer, the thermal effect generated by the second film layer is too strong, resulting in enhanced directivity of the pore size of the porous membrane. This not only causes the pore size of the through holes formed in the second film layer to be too large, thereby increasing the thermal shrinkage rate of the porous membrane and reducing the puncture strength, but also causes a certain short circuit rate in the battery cell.
[0112] 4) By comparing Examples 1 and 6, it can be seen that no matter whether ArF excimer laser or KrF excimer laser is used as the light source, there is no obvious difference in the performance of the porous membrane formed.
[0113] 5) By comparing Examples 1 and 7, it can be seen that whether adding phenyl o-hydroxybenzoate or dihydroxybenzophenone as a UV absorber in the middle film layer is conducive to forming a porous film with a higher tortuosity, among which the UV absorption ability of dihydroxybenzophenone is stronger than that of phenyl o-hydroxybenzoate, and the pore size of the middle layer of the formed porous film is larger.
[0114] 6) By comparing Example 1 and Comparative Example 1, it can be seen that when the ultraviolet absorption capacity of the second film layer is no different from that of the first and third film layers, the through holes in the first, second and third layers of the porous film formed are no different, resulting in a significant increase in the short circuit rate of the battery.
[0115] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A porous membrane, characterized in that It comprises a first porous membrane layer, a second porous membrane layer and a third porous membrane layer which are stacked in sequence; The first porous membrane layer includes a first through hole, the second porous membrane layer includes a second through hole, and the third porous membrane layer includes a third through hole; The first through hole, the second through hole and the third through hole are coaxially arranged, and the aperture of the second through hole is larger than the apertures of the first through hole and the third through hole.
2. The porous membrane according to claim 1, characterized in that The thickness of the second porous membrane layer is 1 to 10 times the thickness of the first porous membrane layer and / or the third porous membrane layer.
3. The porous membrane according to claim 1, characterized in that A ratio of an aperture of the first through hole and / or the third through hole to an aperture of the second through hole is greater than or equal to 0.1 and less than 1.
4. The porous membrane according to any one of claims 1 to 3, characterized in that The second porous membrane layer includes an ultraviolet absorber; Preferably, the mass content of the ultraviolet absorber in the second porous membrane layer is 0.1% to 2%.
5. The porous membrane according to any one of claims 1 to 4, characterized in that The materials of the first porous membrane layer, the second porous membrane layer and the third porous membrane layer independently include one or more of polyethylene terephthalate, polyimide, polybutylene terephthalate, polyethylene naphthalate, polyetheretherketone, polyphenylene sulfide and polybenzimidazole.
6. A method for preparing a porous membrane according to any one of claims 1 to 5, characterized in that: The following steps are involved: 1) co-extruding at least three layers of polymer melts by casting or blow molding to obtain a composite film; wherein the ultraviolet absorption ability of the polymer melt in the middle layer is stronger than that of the polymer melt in the surface layer; 2) Using an ultraviolet laser light source to perform laser drilling on the composite membrane to obtain the porous membrane.
7. The method for preparing a porous membrane according to claim 6, characterized in that: The content of ultraviolet absorber in the polymer melt located in the middle layer is greater than that in the polymer melt located in the surface layer; Preferably, the mass content of the ultraviolet absorber in the polymer melt in the middle layer is 0.1% to 2%.
8. The method for preparing a porous membrane according to claim 6 or 7, characterized in that: The ultraviolet laser light source is selected from one or more of a rare gas excimer laser, a rare gas halide excimer laser, and a halogen gas excimer laser; And / or, the power of a single light source for the laser drilling process is 0.5W to 20W.
9. An electrolyte membrane, characterized in that: The porous membrane comprises the porous membrane described in any one of claims 1 to 5 or the porous membrane prepared by the preparation method described in any one of claims 6 to 8.
10. A battery, characterized in that: Comprising the electrolyte membrane according to claim 9.
Citation Information
Patent Citations
Method for punching micron-grade-diameter hole in film through ultraviolet laser
CN104439721A
Apertured film and method of making an apertured film with a laser
CN106163790A
Improved microporous membranes and devices comprising same
CN116457999A
Multilayer diaphragm for lithium ion battery
CN212147767U
Solid electrolyte membrane, manufacturing method of solid electrolyte membrane, fuel cell having solid electrolyte membrane, and manufacturing method of fuel cell
JP2008084539A
